Analisis Komparatif Kerangka Kerja Manajemen Risiko ISO 31000 dan COSO Enterprise Risk Management (ERM): Studi Literatur - Magdalena Sihotang; Alika Putri; Ulul Azmi Fadhilah; Muhammad Rizal (Jurnal Ilmu Ekonomi dan Bisnis, 2026)
This study aimed to analyze and compare two widely adopted risk management frameworks, namely ISO 31000 and the COSO Enterprise Risk Management (ERM) framework. The research employed a qualitative literature review approach by collecting and examining various scientific sources, including journals, books, and official documents related to risk management. The analysis focused on identifying the concepts, principles, components, strengths, limitations, and implementation implications of both frameworks across different types of organizations. The findings indicated that ISO 31000 offers advantages in terms of flexibility, adaptability, and ease of implementation due to its emphasis on general principles, frameworks, and risk management processes. In contrast, COSO ERM places greater emphasis on integrating risk management with organizational strategy, governance, and performance, thereby supporting strategic decision-making and long-term value creation. Although both frameworks share the same objective of helping organizations manage risks effectively, they differ in their approaches and areas of focus. ISO 31000 is more suitable for organizations requiring a simple and flexible risk management system, whereas COSO ERM is more appropriate for organizations seeking a high level of integration between risk management and strategic objectives. The study also found that combining ISO 31000 and COSO ERM can create a more comprehensive risk management system by leveraging the strengths of both frameworks. Therefore, organizations should select or integrate these frameworks according to their characteristics, risk complexity, and organizational objectives to ensure effective and sustainable risk management.